2020
DOI: 10.3892/ijmm.2020.4649
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑103 modulates tumor progression by targeting KLF7 in non‑small cell lung cancer

Abstract: Numerous studies have identified that microRNAs (miRs) play a crucial role in the tumorigenesis of non-small cell lung cancer (NSCLC). However, to the best of our knowledge, the physiological function of miR-103 in NSCLC is not fully understood. Experiments in the present study revealed that miR-103 expression was increased in NSCLC cell lines. In addition, a series of methods, including MTT, colony formation, 5-ethynyl-2'-deoxyuridine, Transwell, wound healing, flow cytometric, reverse transcription-quantitat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 68 publications
0
15
0
Order By: Relevance
“…[32][33][34][35] miR-103 acts as an oncogene in NSCLC by targeting lncRNA TRHD-AS1, KLF4, and KLF7. 32,36 In DDP-resistant NSCLC cells, the expression of miR-103a-3p is upregulated. 37 miR-103a-3p activates ERK signaling pathway and leads to DDP resistance in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35] miR-103 acts as an oncogene in NSCLC by targeting lncRNA TRHD-AS1, KLF4, and KLF7. 32,36 In DDP-resistant NSCLC cells, the expression of miR-103a-3p is upregulated. 37 miR-103a-3p activates ERK signaling pathway and leads to DDP resistance in NSCLC.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-222-3p stimulates the proliferation and represses apoptosis of non-small-cell lung cancer cells via repressing p53 upregulated modulator of apoptosis (PUMA) ( Chen and Li, 2020 ). A study conducted by Li and Yuan (2020) revealed that miR-103 was elevated in A549 and H1299 cells and promoted cell growth and EMT and reduced cell apoptosis. On the contrary, miR-330 represses the viability, proliferation, and migration of lung cancer cells ( Mohammadi et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al have found that regulating KLF7 can inhibit NSCLC invasion, migration, and EMT (28).…”
Section: Discussionmentioning
confidence: 99%